Pengabdian Mahasiswa untuk Meningkatkan Kesadaran Perilaku Hidup Bersih dan Sehat di Kalangan Santri Pondok Pesantren Darul Aman Tegal - Fatmawati; Muslehudin; Nursyawani; Jamilatul Hasanah; Baiq Nasipah; Ahmad Zulfakar Ali; Auni Islihatin Diniati; Farid Al Rizky; Fatahilah; Hadawiyah; Haerani; Hulwa Rizki Maulidianti; Khansa Ummu Syahidna; Muhammad Azhar; Nadia Rizki (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2024)
Clean and healthy living behaviour is very important to be applied to daily life in boarding schools, this is shown so that each student can adapt and increase everyone's immune system. Based on this awareness, we, the participants of KKN Pondok Pesantren Darul Aman, invite the students to do sports and cleaning activities. The purpose of this service is to provide an understanding to the students that the importance of maintaining health and cleanliness to foster a sense of care for themselves and the environment. Through this service we succeeded in increasing the awareness of the students about clean and healthy living behaviour, and we also succeeded in increasing the awareness of the students to maintain environmental cleanliness in the boarding school